Reward-Punishment sebagai Motivasi Pendidikan (Perspektif Barat dan Islam) - Aziz Aziz (IAIN Ponorogo, 2016)
The study of the association or social interaction in Islamic education serves as the urgent problembecausea good social interaction is likely to affectstudents’ good behavior in a pluralistic society and religious culture. Students’ understanding of this substance has become a very important resource in instilling the inclusive and multicultural education. This article presented and examined the hadiths which were relevant to Islamic educational materialsregarding the instructional issues of social interaction, tolerance, and cooperation such as Muamalah rights and Islamic preaching. The study revealed that the hadiths related to social interaction with non-Muslims had notrecommended to be rude to the non-Muslims if they did not hurt and harm the Muslims. This is consistent with the meaning of Islam itself that is to save and is not to be a device that punishthe people who do not believe in Allah, and Islam should be the spirit of unlimited ocean full of love who is able to frame the diversity in Indonesia.إن التطبيق الصحيح لأسلوب الثواب والعقاب في التربية والتعليم هو من العناصر المهمّة في تكوين الطالب مخلوقا اجتماعيّا، صحيح الجسد وأمينا وواعيا بالمسؤولية في حياته. لذا، فإن تطبيق أسلوب الثواب والعقاب لا بد من الاهتمام بنموّ الطالب نفسيّا مهما كان هذا الأسلوب أصبح قوّة دافعة له. وإن هذا الأسلوب – في نظر الغرب- نوع من التعزيز الإيجابيّ وموخوذ من النظريّة السلوكية. أما في نظر الإسلام فإن هذا الأسلوب نوع من النتائج. وطبقا لبعض من الانتقادات واختلافات الآراء المطروحة،يمكن أن يُقال بأن هناك تناسب بين أسلوب الثواب والعقاب في نظرية التعليم السلوكية وفي التربية الإسلامية، وهي في أنه نتائج من سلوك الطالب وعمله. اتّفق الغرب والإسلام أنّ الثواب والعقاب في التعليم نوع من الدوافع للطالب ليكون نشيطا وناجحا في التعلّم.